Room-temperature direct synthesis of semi-conductive PbS nanocrystal inks for optoelectronic applications - Yongjie Wang (Nature Portfolio, 2019)
Providing large-scale iodide capped semi-conductive PbS nanocrystals inks preparation for high-throughput manufacturing remains a challenge. Here, the authors propose a direct one step and scalable synthesis method enabling cost reduction and promoting its commercial viability for solar cells.